RESPON PEMBERIAN PUPUK ORGANIK CAIR (POC) LIMBAH SAYURAN TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN TOMAT (Lycopersicum esculentum L.) - Widya Lestari (UNIVERSITAS LABUHANBATU, 2019)
The Research Design used was randomized factorial (RAK) group with 1 factors and five levels of treatment: L0:0 ml/plant, L1:125 mL/plant, L2:250 mL/plant, L3:375 mL, 500 ml: L4/plant, and continued with the test Duncan's Multiple Range tests. The parameters observed were higher plants (cm) Weight (kg) pertanaman fruit, fruit diameter. From the results of this research were obtained the following conclusions: (1) the grant of a Liquid organic fertilizer (POC) influential real Vegetables Waste against the plant, fruit weights pertanaman, and the diameter of the fruit. But it has no effect against a real high plants 10 days after planting. Keywords: Waste, production of Vegetables, tomato (Lycopersicum esculentum L.).